Oxygen Variability and Eddy-drivenMeridional Oxygen Supply in the Tropical North East Atlantic Oxygen Minimum Zone - Hahn, Johannes (2013)
The distribution of the mean oceanic oxygen concentration results from a balance between ventilation and consumption and, in particular, reveals extended oxygen minimum zones (OMZ) in the eastern tropical Pacific and Atlantic at intermediate depth (300m - 700m). It has been recently shown that OMZs expand in size and are subject to a significant oxygen decrease, where the OMZ in the Tropical North East Atlantic (TNEA) holds the most significant and largest oxygen trend. This study analyzes hydrographic and velocity data from shipboard and moored observations which were acquired along the 23°W section cutting meridionally through the TNEA OMZ, in order to (i) quantify regional differences in the oxygen variability, (ii) identify the role of two mixing processes (mesoscale stirring and diapycnal mixing) in the production of oxygen variance based on the extended Osborn-Cox model and (iii) estimate the role of mesoscale eddies in the meridional ventilation of the TNEA OMZ. Enhanced oxygen variability is found at the boundaries of the OMZ which is predominantly generated by mesoscale stirring along isopycnals and diapycnal mixing across isopycnals. South of the OMZ core (which is located at about 11°N), mesoscale stirring dominates the generation of oxygen variance, whereas above the OMZ core within the deep oxycline (located at about 300m depth) both processes, mesoscale stirring and diapycnal mixing, are found to be of similar importance. Meridional eddy fluxes of oxygen are estimated by using (i) a diffusive flux parameterization based on a lateral eddy diffusion coefficient and the mean isopycnal oxygen gradient, and (ii) a correlation method based on velocity and oxygen time series from moored observations. At the mooring positions 5°N, 23°W and 8°N, 23°W, the results of both methods are in good agreement in the depth range of the OMZ core, yielding a northward oxygen flux from the well-ventilated equatorial region toward the OMZ core. The divergence of the meridional oxygen flux, as obtained from the diffusive ...